Stability of Pillars and Tabular Excavations under Shear Loading Conditions ? Implications for Mine Planning and Design - Fidelis T. Suorineni (Canadian Institute of Mining, Metallurgy and Petroleum, 2011)
Rockbursts are a major hazard in deep hard rock underground mining and tunneling. To date a significant number of rockbursts still defy conventional explanations. A review of rockburst case histories in the literature has shown that pillars and tabular excavations under shear loading are prone to rockbursting in situations where they are least expected under conventional knowledge of rockburst causes. Despite the evidence of the effects of shear loading on underground infrastructure, and the frequency of their occurrence, little is known about how this loading mechanism causes such large magnitude events and extensive damage. In this paper analytical and numerical modeling are used to understand the behaviour of pillars and tabular excavations under shear loading. The numerical modelling results show that pillars under shear loading are less confined than their equivalents in loaded in pure compression in the same geologic environment, and are therefore more brittle and weak. For tabular excavations under shear loading, the behaviour depends on whether such excavations are continuous, co-planar or offset with rock bridges. Analytical results based on slit theory show releasable potential energy in tabular excavations increases nonlinearly with excavation half-span. The study results are important for the safe and economic extraction of orebodies under shear loading.